Method for the Synthesis of 2H-1,4-Benzoxazin-3-(4H)-ones via Ligand-Free Copper-Catalyzed Cascade Reaction - Zhang, Lingyu; Zhang, Songlin (Synthesis, 2023)
An efficient method for the synthesis of 2H-1,4-benzoxazin-3-(4H)-ones via ligand-free copper-catalyzed cascade reaction of substituted chloroacetamides with 2-halophenols has been developed for the first time. Some of the issues typically encountered during the synthesis of 2H-1,4-benzoxazin-3-(4H)-ones, including adding noble metals and ligands, poor substrate scope, have been addressed using this newly developed ligand-free copper-catalyzed cascade reaction.
Keywords: copper; cross-coupling; ligand-free; Ullmann reaction; 2H-1,4-benzoxazin-3-(4H)-ones